Ultra-sensitive determination of inorganic arsenic valence by solution cathode glow discharge-atomic emission spectrometry coupled with hydride generation. Issue 12 (1st November 2017) - Guo, Xiaohong; Peng, Xiaoxu; Li, Qing; Mo, Jiamei; Du, Yiping; Wang, Zheng
Abstract : A simple and ultra-sensitive method based on HG-SCGD-AES was developed for determination inorganic arsenic valence. Abstract : A simple and ultra-sensitive method for the determination of inorganic arsenic valence was developed by solution cathode glow discharge atomic emission spectrometry (SCGD-AES) coupled with hydride generation (HG). Arsenic was converted into volatile hydrides by the reaction with NaBH4 and HCl, after which they were delivered and subsequently injected into the near-anode region of the SCGD, where they were detected directly by atomic emission spectrometry (AES). The detection limit (DL) for arsenic was improved by four orders of magnitude compared to the single SCGD-AES process. The main operational parameters and sources of potential interference that affect the determination of arsenic were thoroughly studied. Under optimal conditions, the DLs for As(iii ) and As(v ) were both calculated to be 0.3 μg L −1 . Repeatability, expressed as the relative standard deviation of the spectral peak height, was 2.5% ( n = 11) for a 0.1 mg L −1 arsenic solution. The proposed method was validated by the determination of a certified reference material (NIST SRM 1568a) and was applied to the real rice samples, where the measurement results obtained by the HG-SCGD-AES method were in good agreement with the reference values or values from hydride generation atomic fluorescence spectrometry.